Sensory Analysis Of Yoghurt With The Addition Of Genjer Leaf Extract - Putri Farisa Zahara; Anni Faridah; Yuliana Yuliana; Rahmi Holinesti (Universitas Negeri Padang, 2025)
Genjer is a common weed found in agricultural land, especially in areas with sufficient water availability. One way to reduce the presence of genjer is to process it into functional food products, such as genjer leaf extract yogurt, which offers a unique and healthy beverage innovation. The purpose of this study was to analyze the effect of adding genjer leaf extract on the quality of color, aroma, texture, taste and level of preference of yogurt. This type of research is a pure experiment with a Completely Randomized Design (CRD) method involving 4 treatments (0%, 5%, 10%, 15%) and 3 repetitions, with 30 panelists from the Family Welfare Education Study Program Students, Padang State University. Data were analyzed using ANOVA and continued with Duncan's Test if Fcount>Ftable. The results of the study stated that the addition of genjer leaf extract as much as 0%, 5%, 10%, 15% to yogurt had a significant effect on the quality of color (green) and taste (sour). Meanwhile, the quality of aroma (distinctive fragrance of genjer) and texture (slightly thick) did not have a significant effect. The best overall results in this study were shown by adding 10% genjer leaf extract (X2).